New instrumentation for precise (n,γ) measurements at ILL Grenoble - Urban, Waldemar; Jentschel, M.; Märkisch, Bastian; Materna, Th; Bernards, Ch; Drescher, C.; Fransen, Ch; Jolie, J.; Köster, U.; Mutti, P.; Rza̧ca-Urban, T.; Simpson, G. S. (Journal of Instrumentation, 2013)
An array of eight Ge detectors for coincidence measurements of γ rays from neutron-capture reactions has been constructed at the PF1B cold-neutron facility of the Institut Laue-Langevin. The detectors arranged in one plane every 45° can be used for angular correlation measurements. The neutron collimation line of the setup provides a neutron beam of 12 mm in diameter and the capture flux of about 108/(s × cm2) at the target position, with a negligible neutron halo. With the setup up to 109 γγ and up to 108 triple-γ coincidence events have been collected in a day measurement. Precise energy and efficiency calibrations up to 10 MeV are easily performed with 27Al(n,γ)28Al and 35Cl(n,γ)36Cl reactions. Test measurements have shown that neutron binding energies can be determined with an accuracy down to a few eV and angular correlation coefficients measured with a precision down to a percent level. The triggerless data collected with a digital electronics and acquisition allows to determine half-lives of excited levels in the nano- to microsecond range. The high resolving power of double- and triple-γ time coincidences allows significant improvements of excitation schemes reported in previous (n,γ) works and complements high-resolution γ-energy measurements at the double-crystal Bragg spectrometer GAMS of ILL.
Gesehen am 17.02.2022